Quality assessment framework for educational institutions in technical education: a literature survey. Issue 3 (10th September 2018) - Mittal, Raj Kumar; Garg, Namita; Yadav, Sunil Kumar
Abstract : Purpose: This study aims to identify the key indicators for quality enhancement in an educational institute which affect student's outcome in terms of employability and entrepreneurship. These indicators can be used for improving the quality of engineering institutions imparting technical education. Design/methodology/approach: Review of conceptual and empirical literature has been done to establish a linkage between institutional factors and quality output. The paper further identifies existing quality gaps in engineering education that make their students misfit to the requirements of market. Findings: The relevant literature reviewed suggests that quality of technical institutions can be viewed form two perspectives: first, students' achievement in the form of placements, entrepreneurial output, enrollment in higher studies and university ranks. Second, faculty research output in the form of publication in refereed journals, consultancy projects and patents. The study concludes by stating that when these two important stakeholders are provided with the infrastructural support and environment to showcase their skill, the quality of technical institutions improves automatically. Research limitations/implications: The study is conducted on technical institutions engaged in providing engineering education. This research can be extended to other disciplines. Originality/value: The framework proposed in the study will help technical institutions in evaluating their service quality levels which will further help them in improving the same.